Altruism of Shiga toxin-producing Escherichia coli: recent hypothesis versus experimental results - Los, Joanna M.; Los, Marcin; Wegrzyn, Alicja; Wegrzyn, Grzegorz (Frontiers in Cellular and Infection Microbiology, 2013)
Shiga toxin-producing Escherichia coli (STEC) may cause bloody diarrhea and hemorrhagic colitis, with subsequent systemic disease. Since genes coding for Shiga toxins (stx genes) are located on lambdoid prophages, their effective production occurs only after prophage induction. Such induction and subsequent lytic development of Shiga toxin-converting bacteriophages results not only in production of toxic proteins, but also in the lysis (and thus, the death) of the host cell. Therefore, one may ask the question: what is the benefit for bacteria to produce the toxin if they die due to phage production and subsequent cell lysis? Recently, a hypothesis was proposed (simultaneously but independently by two research groups) that STEC may benefit from Shiga toxin production as a result of toxin-dependent killing of eukaryotic cells such as unicellular predators or human leukocytes. This hypothesis could make sense only if we assume that prophage induction (and production of the toxin) occurs only in a small fraction of bacterial cells, thus, a few members of the population are sacrificed for the benefit of the rest, providing an example of ‘bacterial altruism’. However, various reports indicating that the frequency of spontaneous induction of Shiga toxin-converting prophages is higher than that of other lambdoid prophages might seem to contradict the for-mentioned model. On the other hand, analysis of recently published results, discussed here, indicated that the efficiency of prophage excision under conditions that may likely occur in the natural habitat of STEC is sufficiently low to ensure survival of a large fraction of the bacterial host. A molecular mechanism by which partial prophage induction may occur is proposed. We conclude that the published data supports the proposed model of bacterial ‘altruism’ where prophage induction occurs at a low enough frequency to render toxin production a positive selective force on the general STEC population.